Angiogenic biomarkers predict the occurrence of digital ulcers in systemic sclerosis. Issue 3 (15th November 2011) - Avouac, Jérôme; Meune, Christophe; Ruiz, Barbara; Couraud, Pierre Olivier; Uzan, Georges; Boileau, Catherine; Kahan, André; Chiocchia, Gilles; Allanore, Yannick
Abstract : Objective: To evaluate the possible merit of endothelial markers for the prediction of ischaemic digital ulcers in patients with systemic sclerosis (SSc). Methods: Circulating endothelial progenitor cells (EPC), circulating endothelial cells and serum levels of placental growth factor (PlGF), soluble vascular adhesion molecule and vascular endothelial growth factor were measured in a prospective cohort of 100 SSc patients. The primary outcome was the occurrence of one or more new ischaemic digital ulcers during a planned 3-year follow-up. Results: After the follow-up period, 17 patients developed new digital ulcers. By multivariate analysis focused on biomarkers, high PlGF serum levels and low EPC counts were identified as predictors of the occurrence of at least one new digital ulcer. In a secondary model including biomarkers together with clinical SSc characteristics all predictors of digital ulcers defined by p≤0.1 in univariate analysis, high PlGF serum levels (HR 7.26, 95% CI 1.92 to 27.41) and a history of digital ulcers (HR 9.32, 95% CI 1.51 to 59.83) were identified as independent predictors of a new digital ulcer. In an alternative model excluding patients with a history of digital ulcers at baseline, high PlGF serum levels (HR 13.46, 95% CI 1.58 to 114.73) and low EPC counts (HR 7.95, 95% CI 2.09 to 30.09) remained predictive of new digital ulcer occurrence during follow-up. Conclusion: This study identified high PlGF serum levels and low circulating EPC counts as predictors of new digital ulcers in SSc. It highlights the critical role of angiogenesis in this vascular outcome. These markers may improve digital ulcer risk stratification and therefore allow earlier therapeutic intervention.